The Impacts of Global Atmospheric Oscillations on Büyük Menderes and Gediz Streamflows - Emre KEBAPÇIOĞLU; Turgay PARTAL (Doğal Afetler ve Çevre Dergisi)
Recent studies show that global atmospheric circulations are efficient on climate parameters. This study has been carried out to analyze the relationship between the streamflow data in Büyük Menderes/Gediz Basin and the global atmospheric oscillations such as the Southern Oscillation (SO), the North Atlantic Oscillation (NAO) and the Arctic Oscillation (AO). The average annual and seasonal flows at the current 5 stations located in Büyük Menderes basin and Gediz basin, whose measurements were made by the DSI in the 45 year period between 1970 and 2015 have been studied. Then, the relationship between NAO, AO, SO indices and streamflows was determined by correlation analysis. In addition, in order to obtain the periodic components, the original observed data were separated into their components by discrete wavelet transform. The correlations between the found wavelet components (D1, D2, D3, D4 and A) and atmospheric indices were examined. As a result, this study found that there is a strong negative correlation between the streamflow and the AO/NAO indices at the annual/winter and spring period. Moreover, the wavelet periodic components showed to the main factors for the relationship of the streamflow data with the global atmospheric patterns.